Ionic Art and Script in Archaic Macedonia: Origin(s), Medium(s), Effect(s) - Boufalis, Angelos (Tekmeria, 2024)
It is widely assumed that Macedonia in the late Archaic period was under East Greek influence. This view was formed decades ago, based on scant evidence, but has since been established through repetition and persists despite the growing number of reported and published finds that indicate otherwise. In this paper I intend to challenge this opinio communis and to reframe the issue of Ionic influence in archaic Macedonia within the wider Northern Aegean context. To this end, the relevant pieces of evidence are reviewed, focusing on works of sculpture in the Ionic style and inscriptions in Ionic script, but also examining the coinage in the name of Alexander I. In short, it is demonstrated that the available pieces of evidence do not support widespread East Greek influence in Macedonia in the late Archaic period and it is argued that it was rather through the Cycladic colonies in the Strymonic Gulf that Ionic art reached Macedonia; that mostly Ionians from these colonies were responsible for the inscriptions in Ionic script in Macedonia; and that it was possibly a Central, not East, Ionic script that was employed on Alexander I’s coinage.